CREB: A Multifaceted Target for Alzheimer’s Disease - Sharma, Vivek K.; Singh, Thakur G. (Current Alzheimer Research, 2020)
Alzheimer’s disease (AD) is a persistent neuropathological stipulation manifested in the form of neuronal/synapse demise, the formation of senile plaques, hyperphosphorylated tau tangles, neuroinflammation, and apoptotic cell death. The absence of a therapeutic breakthrough for AD has continued the quest to find a suitable intervention. Apart from various candidates, the cyclic AMPprotein kinase A-cAMP response element-binding protein (cAMP/PKA/CREB) pathway is the most sought-after drug target AD as the bulk of quality literature documents that there is downregulation of cAMP signaling and CREB mediated transcriptional cascade in AD. cAMP signaling is evolutionarily conserved and can be found in all species. cAMP response element-binding protein (CREB) is a ubiquitous and integrally articulated transcription aspect that regulates neuronal growth, neuronal differentiation/ proliferation, synaptic plasticity, neurogenesis, maturation of neurons, spatial memory, longterm memory formation as well as ensures neuronal survival. CREB is a central part of the molecular machinery that has a role in transforming short-term memory to long-term. Besides AD, impairment of CREB signaling has been well documented in addiction, Parkinsonism, schizophrenia, Huntington’s disease, hypoxia, preconditioning effects, ischemia, alcoholism, anxiety, and depression. The current work highlights the role and influence of CREB mediated transcriptional signaling on major pathological markers of AD (amyloid β, neuronal loss, inflammation, apoptosis, etc.). The present work justifies the continuous efforts being made to explore the multidimensional role of CREB and related downstream signaling pathways in cognitive deficits and neurodegenerative complications in general and AD particularly. Moreover, it is reaffirmed that cyclic nucleotide signaling may have vast potential to treat neurodegenerative complications like AD.
Keywords: Alzheimer' s disease